The 2014 European Inventory of validation of non-formal and informal learning : Prospects and trends of validation in Europe - Villalba-Garcia, Ernesto [Verfasser]; Souto-Otero, Manuel [Verfasser] (My University, 2014)
"The European Inventory is a tool produced under the auspices of the European Commission and has been in place since 2004. It presents an overview of the situation regarding validation in European countries. The 2014 Inventory investigates 33 countries through 36 country reports. After describing the political context for the validation of non-formal and informal learning in Europe, namely the European Council Recommendation of December 2012, the article explains the main features of the European Inventory and presents selected findings." (Autorenreferat, BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; S 2.3 Berufsbildungspolitik; I 2.2 Europa; Non-formales Lernen; Informelles Lernen; Anerkennung; EU-Bildungspolitik